ESTHER GREENWOOD MENTAL DISORDER IN SYLVIA PLATH'S NOVEL THE BELL JAR - Desyana, Vella Nandita; Saprudin, Saprudin (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
This article discusses the mental disorder experienced by Esther Greenwood as the main character in the novel The Bell Jar by Sylvia Plath. This study was conducted to reveal the picture of mental disorders experienced by Esther Greenwood by analyzing the symptoms of depression experienced by her. The approach used in this research is literary psychology with qualitative descriptive methods. Based on research using the theory from Lubis (2016), the symptoms of depression character Esther Greenwood in the novel The Bell Jar are emotional symptoms, cognitive symptoms, fear symptoms and psychic symptoms.Keywords: Depression, Mental Disorders, Literary Psychology, The Bell Jar.